The role of celebrity endorsement and its effect on purchase intention - Marques, Ana Carolina de Almeida (2023)
Through the years, it has become clear that celebrity endorsement is an essential part of any effective marketing plan for a company. Subsequently, one of the most crucial techniques to reach the target audience and differentiate the business from the competition is certainly creating successful communication strategies. As a result, the main goal of this dissertation is to understand how the use of celebrities in advertisements—or the lack thereof—can affect consumers' intentions to buy a brand's product. In this way, celebrity endorsement will be treated as an independent variable, while purchase intention will be handled as a dependent variable. Additionally, brand equity will be included in the conceptual framework as a mediator between the two previously mentioned variables. Later, through a survey in which participants faced one of six stimuli, quantitative data was gathered and, posteriorly, analyzed though IBM SPSS. This way, respondents were prompted to respond to some questions concerning celebrity selection, rate twentythree brand equity statements, and indicate on a fivepoint Likert scale whether they intended to purchase the brand that was being promoted. Contrary to what was concluded by the literature, using celebrities in advertisements does not appear to boost brand equity or purchase intention. This was confirmed by the completion of independent samples TTests, which demonstrated that there was no significant relationship between the variables. Additionally, it doesn't seem that brand equity significantly mediates celebrity endorsement and purchase intention.